A modulatory role of ASICs on GABAergic synapses in rat hippocampal cell cultures. Issue 1 (December 2016) - Storozhuk, Maksim; Kondratskaya, Elena; Nikolaenko, Lyudmila; Krishtal, Oleg
Abstract Rapid acidification occurring during synaptic vesicle release can activate acid-sensing ion channels (ASICs) both on pre- and postsynaptic neurons. In the latter case, a fraction of postsynaptic current would be mediated by cation-selective acid-sensing ion channels. Additionally, in both cases, activation of acid-sensing ion channels could modulate synaptic strength by affecting transmitter release and/or sensitivity of postsynaptic receptors. To address potential involvement of acid-sensing ion channels in mediation/modulation of synaptic transmission at hippocampal GABAergic synapses, we studied effects of three structurally different blockers of acid-sensing ion channels on evoked postsynaptic currents using the patch-clamp technique. We found that GABAergic postsynaptic currents, recorded below their reversal potential as inward currents, are suppressed by all the employed blockers of acid-sensing ion channels. These currents were suppressed by 20 % in the presence of a novel blocker5b (1 μM) and by 30 % in the presence of either amiloride (25 μM) or diminazene (20 μM). In the same cells the suppression of postsynaptic currents, recorded above their reversal potential as outward currents was statistically insignificant. These results imply that the effects of blockers in our experiments are at least partially postsynaptic. On the other hand, in the case of mediation of a fraction of postsynaptic current by acid-sensing ion channels, an increase of outward currents would be expected under our experimental conditions. Our analysis of a bicuculline-resistant fraction of postsynaptic currents also suggests that effects of the blockers are predominantly modulatory. In this work we present evidence for the first time that acid-sensing ion channels play a functional role at hippocampal GABAergic synapses. The suppressing effect of the blockers of acid-sensing ion channels on GABAergic transmission is due, at least partially, to a postsynaptic but (predominantly) modulatory mechanism. We hypothesize that the modulatory effect is due to functional crosstalk between ASICs and GABAA -receptors recently reported in isolated neurons, however, verification of this hypothesis is necessary.